2023
DOI: 10.1021/acsami.3c12885
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on the Interface Structure, Mechanical Properties, and Thermal Stability of TiAlSiN/TiAlN Multilayers

Jian W. Du,
Jie Zhang,
Li Chen
et al.

Abstract: Recently, the TiAlSiN/TiAlN coatings with excellent mechanical and thermal properties have great potential for protective applications that face deteriorated service environments. Here, we systematically investigate the interface structure, mechanical properties, and thermal stability of TiAlSiN/TiAlN multilayers with varied Al and Si contents of TiAlSiN sublayer. B o t h T i 0 . 5 3 A l 0 . 3 8 S i 0 . 0 9 N / T i 0 . 5 2 A l 0 . 4 8 N ( M L _ 1 ) a n d Ti 0.48 Al 0.38 Si 0.14 N/Ti 0.52 Al 0.48 N (ML_2) exhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 64 publications
0
1
0
Order By: Relevance
“…Magnetron sputtering is a highly recommended technique for depositing various industrial coatings. , It contributes to a wide application range, including wear-resistant, hard, corrosion-resistant, oxidation-resistant, and decorative coatings with specific optical or electrical properties. It is often used to improve the performance and extend the lifetime of different components such as cutting tools, aircraft fasteners, and proton exchange membrane fuel cells. Transition metal nitride films have shown good corrosion resistance, high hardness, and excellent electrical conductivity. Among them, titanium nitride is widely used in manufacturing cutting tools, orthopedic implants, stamping tools, and bearings and as a decorative material. , Many researchers have found that TiN coatings are usually characterized by high tribological performance during friction by forming a solid lubricant. Therefore, combining TiN coatings with other elements (e.g., Al, Mo, Cr, etc.) presents a remarkable improvement in the hardness and wear resistance.…”
Section: Introductionmentioning
confidence: 99%
“…Magnetron sputtering is a highly recommended technique for depositing various industrial coatings. , It contributes to a wide application range, including wear-resistant, hard, corrosion-resistant, oxidation-resistant, and decorative coatings with specific optical or electrical properties. It is often used to improve the performance and extend the lifetime of different components such as cutting tools, aircraft fasteners, and proton exchange membrane fuel cells. Transition metal nitride films have shown good corrosion resistance, high hardness, and excellent electrical conductivity. Among them, titanium nitride is widely used in manufacturing cutting tools, orthopedic implants, stamping tools, and bearings and as a decorative material. , Many researchers have found that TiN coatings are usually characterized by high tribological performance during friction by forming a solid lubricant. Therefore, combining TiN coatings with other elements (e.g., Al, Mo, Cr, etc.) presents a remarkable improvement in the hardness and wear resistance.…”
Section: Introductionmentioning
confidence: 99%